PERCEIVED KNOWLEDGE, ATTITUDE AND PRACTICE REGARDING WASTE MINIMIZATION AND ENERGY RECOVERY: ASTUDYOF IJEBU ODE METROPOLIS - OGUNYANWO O. O, OGUNYANWO O. O (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
The purpose of this study was to assess the knowledge, attitude and practice of inhabitants of the high and low density areas of Ijebu-ode metropolis with respect to waste minimization and energy recovery. The study used 240 sampled inhabitants (120 in the high and 120 in the low density area) of Ijebu-ode. The instrument used was a validated questionnaire with likert type scale. Descriptive statistics of mean and standard deviation were used and the inferential statistics of "z"-test also used totest the three hypotheses at 0.05 significant level. All the hypotheses were accepted as there were no significant difference in the knowledge, attitude and practice of respondents of the high and low density areas of Ijebu-ode metropolis with respect to waste minimization and energy recovery. It was recommended that government should enact laws and establish policies that engender positive attitudes towards waste minimization at all levels.